Regulating Mechanotransduction in Three Dimensions using Sub‐Cellular Scale, Crosslinkable Fibers of Controlled Diameter, Stiffness, and Alignment. (26th March 2019) - Wang, Mingkun; Cui, Chunxiao; Ibrahim, Mazen Mohamed; Han, Biao; Li, Qing; Pacifici, Maurizio; Lawrence, John Todd R.; Han, Lin; Han, Li‐Hsin
Abstract: The extracellular matrix (ECM) is a complex 3D framework of macromolecules, which regulate cell bioactivity via chemical and physical properties. The ECM's physical properties, including stiffness and physical constraints to cell shape, regulate actomyosin cytoskeleton contractions, which induce signaling cascades influencing gene expression and cell fate. Engineering such bioactivity, a.k.a., mechanotransduction, has been mainly achieved by 2D platforms such as micropatterns. These platforms cause cytoskeletal contractions with apico‐basal polarity and can induce mechanotransduction that is unnatural to most cells in native ECMs. An effective method to engineer mechanotransduction in 3D is needed. This work creates FiberGel, a 3D artificial ECM comprised of sub‐cellular scale fibers. These microfibers can crosslink into defined microstructures with the fibers' diameter, stiffness, and alignment independently tuned. Most importantly, cells are blended amongst the fibers prior to crosslinking, leading to homogeneously cellularized scaffolds. Studies using mesenchymal stem cells showed that the microfibers' diameter, stiffness, and alignment regulate 3D cell shape and the nuclei translocation of transcriptional coactivators YAP/TAZ (yes‐associated protein/transcriptional coactivator), which enables the control of cell differentiation and tissue formation. A novel technology based on repeated stretching and folding is created to synthesize FiberGel. This 3D platform can significantly contribute to mechanotransduction research and applications. Abstract : A novel platform to enable the control of three‐dimensional (3D) cell shape and how cells perceive the mechanical properties of a 3D microenvironment is developed. This platform is comprised of microfibers thinner than the typical size of cells (≈10 µm), which can be crosslinked in the presence of cells into 3D microstructures, in which fiber diameter, stiffness, and alignment regulate cell bioactivity.